Strategies in Preventing Raw Material Inventory Fraud - Mardianih, Dea; Lasmana, Andy; Aziz, Ayi Jamaludin (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to determine the effect of internal inventory control, accounting information systems, morality and distributive justice on fraud prevention. The population in this study were employees who worked in the warehouse department at PT Yongjin Javasuka Garment. The sampling technique in this study uses a census or total sample technique where each element of the population members is selected into a sample of 50 people. The data collection method was carried out by distributing questionnaires to all samples that had been selected as research respondents. Data analysis was carried out using multiple linear regression analysis techniques. This technique is used to test the research hypothesis that has been formulated, with the aim of knowing the relationship and influence of the independent variable on the dependent variable. JASP software version 0.18.3.0 is used to assist in the data analysis process, because this software provides the statistical tools needed to perform multiple linear regression effectively. The results of this study indicate that internal inventory control and distributive justice partially affect fraud prevention. Meanwhile, the accounting information system and morality have no partial effect on fraud prevention.